The Liability of the Parties for Unstated Clauses from the Perspective of Legal Certainty - Putri Agustina; Dadan Taufik Fathurohman (Riviera Publishing, 2026)
Contracts, which serve as the basis for legal relationships between parties, often contain clauses that are not clearly disclosed to one of the parties. The existence of such hidden clauses has the potential to create injustice and harm parties with weaker bargaining positions. This is a significant issue from the perspective of legal certainty because it may affect the validity and enforceability of contracts. This study aims to analyze the liability of the parties regarding undisclosed clauses and examine their implications for legal certainty in contractual relationships. This study employs an empirical legal research method, focusing on the effectiveness and application of legal provisions in society. The data used consist of primary and secondary legal materials, which were analyzed qualitatively. The results of the study indicate that undisclosed clauses violate the principle of good faith and may lead to an imbalance of rights and obligations between the parties. Such clauses may be declared invalid or void because they fail to fulfill the requirements of a valid agreement. Furthermore, the aggrieved party has the right to pursue legal remedies.